Dynamics of Severe and Non-severe Invasive Pneumococcal Disease in Young Children in Israel Following PCV7/PCV13 Introduction. Issue 10 (October 2018) - Glikman, Daniel; Dagan, Ron; Barkai, Galia; Averbuch, Diana; Guri, Alex; Givon-Lavi, Noga; Ben-Shimol, Shalom
Abstract : Background: The introduction of the pneumococcal conjugated vaccines (PCVs) resulted in a substantial reduction of invasive pneumococcal disease (IPD) rates. However, impact on nonsevere IPD (mostly occult bacteremia) has not yet been fully elucidated. We assessed severe and nonsevere IPD (SIPD and NSIPD, respectively) rate dynamics in children < 5 years in Israel before and after PCV7/PCV13 implementation. Methods: A prospective, population-based, nationwide surveillance. All IPD episodes recorded from 1999 through 2015 were included. NSIPD was defined as IPD episodes without meningitis, pneumonia or mastoiditis in a child with a favorable outcome (not hospitalized or hospitalized in a nonintensive care unit < 5 days, without mortality). Three subperiods were defined: pre-PCV (1999–2008), PCV7 (2010–2011) and PCV13 (2013–2015). Incidence rate ratios (IRRs) were calculated. Results: Overall, 4, 457 IPD episodes were identified; 3, 398 (76.2%) SIPD, 1, 022 (22.9%) NSIPD and 37 (0.8%) unknown. In 90% of NSIPD episodes, no focus was identified. In the PCV7 period, NSIPD rates significantly declined by 52%, while SIPD rates declined less prominently by 24%. Following PCV13 introduction, compared with the PCV7 period, NSIPD rates declined nonsignificantly by 17% while SIPD rates declined significantly further by an additional 53%. These trends resulted in overall reductions (comparing PCV13 and pre-PCV periods) of NSIPD and SIPD of 60% (IRR = 0.4; 0.32–0.51) and 64% (IRR = 0.36; 0.32–0.42), respectively. Conclusions: Following PCV7/PCV13 introduction, SIPD and NSIPD rates substantially declined, with differences in rate-dynamics, alluding to differences in serotype distribution between the 2 groups. Future surveillance is warranted when considering modification in treatment protocols for suspected occult bacteremia/NSIPD cases. Abstract : Supplemental Digital Content is available in the text.